2018
DOI: 10.1016/j.ijheh.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of organophosphate pesticide exposure in pregnant women: A population-based cohort study in the Netherlands

Abstract: Background In the Netherlands organophosphate (OP) pesticides are frequently used for pest control in agricultural settings. Despite concerns about the potential health impacts of low-level OP pesticides exposure, particularly in vulnerable populations, the primary sources of exposure remain unclear. The present study was designed to investigate the levels of DAP metabolites concentrations across pregnancy and to examine various determinants of DAP metabolite concentrations among an urban population of women i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 74 publications
(122 reference statements)
6
46
0
Order By: Relevance
“…In regard to the biological plausibility of our findings, we found that lean women have higher DAP metabolites ( median: vs. ) than overweight/obese women, which was consistent with the results from previous studies ( Llop et al. 2017 ; Van den Dries et al. 2018 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In regard to the biological plausibility of our findings, we found that lean women have higher DAP metabolites ( median: vs. ) than overweight/obese women, which was consistent with the results from previous studies ( Llop et al. 2017 ; Van den Dries et al. 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…In regard to the biological plausibility of our findings, we found that lean women have higher DAP metabolites (R 4 DAP median: 243:84 nmol=g vs. 219:15 nmol=g) than overweight/ obese women, which was consistent with the results from previous studies (Llop et al 2017;Van den Dries et al 2018). We could infer that lean women tend to have a healthier lifestyle, with more FV in their diet, which may result in higher DAP concentrations.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, maternal dietary intake in the first trimester was assessed using a modified version of a validated semiquantitative food frequency questionnaire (FFQ), and the 293 food items were reduced to 24 predefined food groups (e.g., meat, grains, vegetables, fruits) according to the European Prospective Investigation into Cancer and Nutrition (EPIC)–soft classification, based on origin, culinary usage, and nutrient profiles (Steenweg-de Graaff et al. 2012; van den Dries et al. 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Third, models truncating the bottom and top 3% of exposure and child nonverbal IQ values were fit to test data robustness. Fourth, the primary models were adjusted for fruit and vegetable intake (van den Dries et al. 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation